HUBUNGAN FREKUENSI PENERBANGAN DENGAN INTENSITAS KEBISINGAN DI BANDARA INTERNASIONAL MINANGKABAU - Safira Putri Indraswari; Onny Setiani; Budiyono Budiyono (Jurnal Kesehatan Masyarakat (Undip), 2021)
Flight activities can produce a noise and give an impact to human health and environmental health. Minangkabau International Airport is an airport with a high flight frequency category, the average of total flights number is 60 flight activities for a day. This study aimed to analyze of association between flight frequency and noise intensity at Minangkabau International Airport.This type of research was an analytic research with cross sectional approach Samples using in this study were 24 samples which were taken by quota sampling technique. Noise intensity was measured using a Sound Level Meter. Data analysis was performed using Chi Square test (α=5%). The result found that the highest average flight frequency was 17 flights within a three hours period, the highest noise intensity measurement results was 90.4 dB(A) and as many as 14 noise measurement points exceed NAB (NAB=85 DB(A)) Based on the results of the chi square test (p = 0.010) there was a significant relationship between flight frequency and noise intensity at Minangkabau International Airport. The conclusion of this study is that Noise intensity in Minangkabau Internasional Airport exceed NAB and there is a significant relationship between flight frequency and noise intensity